Sportmedizin im Wandel - Ewers SM; Halioua R; Jäger M; Seifritz E; Claussen MC (Dynamic Media Sales Verlag, 2017)
Disturbed Eating Behavior and Eating Disorders are among the most common mental health problems and diseases in high-performance sports. In addition to the classic eating disorders that are classified in ICD-10 and DSM-5 other phenotypes of disturbed eating behavior play an important role in high-performance sport. Sports-specific disturbed eating behavior and eating disorders can be depicted in the concept of the Female Athlete Triad (energy availability, menstrual status and bone health).The phenotypesof specific disorders of eating behavior in sports are presented: Anorexia athletica, Exercise-bulimia, Adipositas athletica, muscular dysmorphia and orthorexia and co-morbid disorders are presented. Subsequently, frequencies and risk factors for the development of a disturbed eating behavior are presented, which vary depending on type of sport and gender. Finally, diagnostics and treatment of disturbed eating behavior in high-performance sports are highlighted.So far,there is no unified classification of disturbed eating behavior in high-performance sports. Until now there is a lack of long-term studies concerning the course of disturbed eating behavior and eating disorders among athletes. In addition, the variety of used research tools limit the validity and comparability of studies. Published statements and position papers on disturbed eating behavior and eating disorders in high-performance sports can be applied to the situation in Germany. However, further research is required in order to develop valid screening instruments and to improve treatment and care for athletes.KEY WORDS: High-Performance Sports, Female Athlete Triad, Eating Disorders, Risk Factors